2022
DOI: 10.1590/0001-3765202220200752
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of β-galactosidase produced by Kluyveromyces lactis by ion-exchange chromatography: Influence of pH and ionic strength parameters

Abstract: The use of β-galactosidase in food products has been a major focus of the industry. Therefore, the development of effi cient and inexpensive methodologies to purify it is essential. Thus, this study aimed to recover the enzyme β-galactosidase (β-gal) by ion-exchange chromatography in a fi xed-bed column. Batch adsorption tests were performed using four types of adsorbents. The β-gal adsorption capacity in batch mode using Streamline DEAE resin presented the best performance, with a retention capacity of 18.77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…In a further, SDS profiles indicated that the molecular weight of lactase was about 120 kDa and that of glucose isomerase was about 70 kDa. The relative molecular mass of glucose isomerase reported in the relevant literature was about 63 kDa [ 62 ] and the molecular weight of lactase was between about 60 and 120 kDa [ 61 , 63 ], similar to the results we obtained.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In a further, SDS profiles indicated that the molecular weight of lactase was about 120 kDa and that of glucose isomerase was about 70 kDa. The relative molecular mass of glucose isomerase reported in the relevant literature was about 63 kDa [ 62 ] and the molecular weight of lactase was between about 60 and 120 kDa [ 61 , 63 ], similar to the results we obtained.…”
Section: Resultssupporting
confidence: 90%
“…Figure S2A,B both show only one band, indicating that all protein in both crude extracts corresponded to these enzymes. Thus, it was feasible for us to calculate the immobilization efficiency by determining the total protein content of the initial enzyme solution [ 60 , 61 ]. In a further, SDS profiles indicated that the molecular weight of lactase was about 120 kDa and that of glucose isomerase was about 70 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been successfully employed for the purication of different recombinant proteins for various purposes. [53][54][55][56][57] The molecular mass of puried recombinant esterase enzyme was 29 kDa as analyzed by SDS-PAGE (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…An exception from it, the 150 kDa ultrafiltration (UF) membrane is used for recovering a 135 kDa b-galactosidase of K. lactis origin (Maxilact LX 5000) by Pocedicova ´et al [39]. The molecular weights of the enzymes responsible for transgalactosylation are reported to be between 90 and 240 kDa for B. circulans [43], between 120 kDa and 140 kDa for K. lactis [45], and ca. 105 kDa for A. oryzae [46].…”
Section: Enzyme Recoverymentioning
confidence: 99%